Eosinophilic ulcer mimicking malignancy of the lower lip: A case report - Ghasem Rahmatpour Rokni; Sidharth Sonthalia; Dipali Rathod; Torello Lotti; Mohamad Goldust (Clinical Case Reports, 2020)
Abstract Eosinophilic ulcer (EU) is a rare self‐limiting chronic benign lesion of the oral mucosa. It is an uncommon and benign disease, which may leading to diagnostic difficulties. Biopsy is recommended to rule out any malignant etiology.